Determinants of Antibiotic Tailoring in Pediatric Intensive Care: A National Survey*. Issue 9 (September 2017) - Fontela, Patricia S.; Quach, Caroline; Karim, Mohammad E.; Willson, Douglas F.; Gilfoyle, Elaine; McNally, James Dayre; Gonzales, Milagros; Papenburg, Jesse; Reynolds, Steven; Lacroix, Jacques
Abstract : Objectives: To describe the criteria that currently guide empiric antibiotic treatment in children admitted to Canadian PICUs. Design: Cross-sectional survey. Setting: Canadian PICUs. Subjects: Pediatric intensivists and pediatric infectious diseases specialists. Interventions: None. Measurements and Main Results: We used focus groups and literature review to design the survey questions and its four clinical scenarios (sepsis, pneumonia, meningitis, and intra-abdominal infections). We analyzed our results using descriptive statistics and multivariate linear regression. Our response rate was 60% for pediatric intensivists (62/103) and 36% for pediatric infectious diseases specialists (37/103). Variables related to patient characteristics, disease severity, pathogens, and clinical, laboratory, and radiologic infection markers were associated with longer courses of antibiotics, with median increment ranging from 1.75 to 7.75 days. The presence of positive viral polymerase chain reaction result was the only variable constantly associated with a reduction in antibiotic use (median decrease from, –3.25 to –8.25 d). Importantly, 67–92% of respondents would still use a full course of antibiotics despite positive viral polymerase chain reaction result and marked clinical improvement for patients with suspected sepsis, pneumonia, and intra-abdominal infection. Clinical experience was associated with shorter courses of antibiotics for meningitis and sepsis (–1.3 d [95% CI, –2.4 to –0.2] and –1.8 d [95% CI, –2.8 to –0.7] per 10 extra years of clinical experience, respectively). Finally, site and specialty also influenced antibiotic practices. Conclusions: Decisions about antibiotic management for PICU patients are complex and involve the assessment of several different variables. With the exception of a positive viral polymerase chain reaction, our findings suggest that physicians rarely consider reducing the duration of antibiotics despite clinical improvement. In contrast, they will prolong the duration when faced with a nonreassuring characteristic. The development of objective and evidence-based criteria to guide antibiotic therapy in critically ill children is crucial to ensure the rational use of these agents in PICUs. Abstract : Supplemental Digital Content is available in the text.